Profiling individual discussants' behaviours in online asynchronous discussions - Elizabeth Murphy; Maria A Rodriguez Manzanares (The Canadian Network for Innovation in Education (CNIE), 2006)
This paper provides an illustrative example of an approach to creating and reporting individual profiles of engagement in particular behaviours in an online asynchronous discussion (OAD). Individual results of analysis of transcripts of an OAD can provide insights different from those gained by focusing on aggregate measures of group behaviours. In this case, we focused on individual behaviours associated with Problem Formulation and Resolution (PFR) in a one-month long OAD with seven graduate students. The transcripts of each participant were analysed for patterns of PFR behaviours using a previously designed instrument. Individual profiles of the seven participants were created. The paper provides examples of how the approach facilitated identification and comparison of individual weaknesses and strengths. Also provided are examples of how individual profiles might be useful in professional development and instructional contexts for formative or summative assessment purposes.